2018
DOI: 10.1371/journal.pgen.1007737
|View full text |Cite
|
Sign up to set email alerts
|

Filamentation of asparagine synthetase in Saccharomyces cerevisiae

Abstract: Asparagine synthetase (ASNS) and CTP synthase (CTPS) are two metabolic enzymes crucial for glutamine homeostasis. A genome-wide screening in Saccharomyces cerevisiae reveal that both ASNS and CTPS form filamentous structures termed cytoophidia. Although CTPS cytoophidia were well documented in recent years, the filamentation of ASNS is less studied. Using the budding yeast as a model system, here we confirm that two ASNS proteins, Asn1 and Asn2, are capable of forming cytoophidia in diauxic and stationary phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…The protein seen in five stresses, Asns, has been reported to form filaments in yeast under stress (65), suggesting it also is functionally remodeled in the stress response. When we consider the solubility changes in proteins found in, at least, three stresses in terms of KEGG pathways, we observed a clustering into core metabolic pathways of lipid metabolism, carbohydrate metabolism, nucleotide metabolism, amino acid metabolism, and energy metabolism (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The protein seen in five stresses, Asns, has been reported to form filaments in yeast under stress (65), suggesting it also is functionally remodeled in the stress response. When we consider the solubility changes in proteins found in, at least, three stresses in terms of KEGG pathways, we observed a clustering into core metabolic pathways of lipid metabolism, carbohydrate metabolism, nucleotide metabolism, amino acid metabolism, and energy metabolism (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence indicates that CTPS is not the only component of these filaments. We previously reported that inosine monophosphate dehydrogenase (IMPDH), the rate-limiting enzyme in de novo GTP biosynthesis, and asparagine synthetase (ASNS), an essential enzyme for biosynthesis of asparagine, can be assembled into similar filaments adjacent to the CTPS cytoophidium 20,21 . It may be that CTPS cytoophidia serves as a metabolic stabilizer and a cooperative platform for CTPS and many other metabolic enzymes.…”
mentioning
confidence: 99%
“…Several studies have shown that CTPS compartmentalizes into filamentous structures in various organisms, including bacteria, fruit fly, rat and human cells (Ingerson-Mahar et al., 2010; Liu, 2010; Noree et al., 2010; Carcamo et al., 2011; Chen et al., 2011). It has also been reported that CTPS filaments can be observed in budding yeast (Noree et al., 2010, 2014; Shen et al., 2016; Zhang et al., 2018). We have previously identified that CTPS forms cytoophidia in S. pombe (Zhang et al., 2014; Li et al., 2018).…”
Section: Discussionmentioning
confidence: 73%